Supercritical fluid extraction of date seed oil - Mohd Jaih, Abdul Afiq; Abdul Rahman, Russly; Abdull Razis, Ahmad Faizal; Ariffin, A. A.; Al-Awaadh, A.; Selamat, Jinap (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Date seed is a by-product of date fruit (Phoenix dactylifera) industry. It is normally being discarded as waste or traditionally processed into animal feed or caffeine-free coffee in small scale. In this study, seed from Mabroum date variety was cleaned and grinded, and oil was extracted using supercritical fluid extraction method at pressure range from 20 to 40 MPa and temperature range from 40 to 70 ºC. The extraction was last for 120 mins and flowrate of carbon dioxide, the supercritical fluid was made constant at 5 ml/min. Supercritical fluid extraction that was performed at combination of 20 MPa and 40 ºC resulted in the highest oil yield and recovery. Oil recovery ranged from 4.3 to 8.1 %, while oil yield ranged from 52.4 to 99.2 %. Oleic acid was found as the major fatty acid present in the date seed oil. However, different combination of temperature and pressure in supercritical fluid extraction resulted in different fatty acid composition of the oil.